In Their Voices: Client and Staff Perceptions of the Physical and Social Environments of Adult Day Services Centers in Taiwan. (29th July 2018) - Liou, Chih-ling; Jarrott, Shannon
Abstract : Studies have examined the impact of environments on long-term care residents' quality of life; however, environment gets little attention in adult day services (ADS). The current study gives voice to clients and staff by capturing their perceptions of the physical and social environments of their ADS centers. Data were collected from 23 interviews with staff and clients and 270 hours of participant observations at two ADS centers in Taiwan. The authors triangulated field notes with interview transcriptions and analyzed them with the Grounded Theory coding procedure method. Findings reveal clients' and staff members' perceptions of appropriate and inappropriate physical and social environmental features affecting quality of life at the center and reflecting Taiwanese culture. We address how perceived appropriate features can be sustained or replicated and how perceived inappropriate influences can be remedied. Results can be translated into action research by implementing supportive environments for both staff and clients at ADS centers.